Australian bustard - Ziembicki, Mark (Australian natural history series., 2010)
The Australian bustard is Australia's heaviest flying bird. It is an icon of theAustralian outback where it is more commonly known as the bush or plains turkey. Itis also culturally and spiritually significant to Aboriginal people, who prize it as afavourite bush tucker.